RAGAM TRADISI PENJAGAAN AL-QUR’AN DI PESANTREN : (Studi Living Qur’an di Pesantren Al-Munawwir Krapyak, An-Nur Ngrukem, dan Al-Asy’ariyyah Kalibeber) - Anisah Indriati (AL ITQAN: Jurnal Studi Al-Qur'an, 2017)
One of the most popular studies discussed in the Qur'anic study today is called living Qur'an. Although its phenomenological cultural nuances, but it is still included in the study of scriptures. Since living Qur'an is basically began from the phenomenon of the Qur'an in Every Day Life. This study discusses not focused on study of texts of the Qur'an, but in realm of the importance and practical function of the Qur'an in Muslim society. There are pesantrens of al-Qur'an which, in fact, make an important contribution in developing and improving Muslims interaction on the Qur'an. Their roles in creating hundreds or even more than thousands HuffÄáº“ al-Qur'an have proven their existences in living Qur'an. Many varieties of methods of and processes of the interaction have been done, so that Qur'an become into a live "entity" among muslim community generally and especially for students of pesantren. There are three popular pesantrens have been creating HuffÄáº“ al-Qura'n, called Pesantren al-Munawwir Krapyak Yogyakarta, Pesantren Tahfiáº“ al-Qur'an al-Asy'ariyah Kalibeber Wonosobo, Central Java, and Pesantren An-Nur Ngrukem Bantul. All these three Islamic boarding school have proven their existence are considered very important in creating society to love al-Qur'an. It becomes important to be discussed, because the study now sought to find out how that pesantrens community interact with the Qur'an. So that the fundamental values of the Qur'an can be manifested in every muslim daily activities and then can always brings spiritual charges to thier soul.